Smoking habits among medical students: a survey at the University of Prishtina Faculty of Medicine - Fejza, Albina; Maraj, Fatjeta; Fejza, Hajrullah (International Journal of Medical Students, 2018)
Background: Smoking is a common habit among the population in Kosovo. In the country, smoking occurs in public places, health and educational institutions despite being prohibited by law. Our objective was to describe smoking habits, knowledge and attitudes among medical students from all departments in the University of Prishtina, Faculty of Medicine. Methods: The present study followed the Global Health Professions Student Survey (GHPSS) standardized methodology including data processing procedures. A self-administered questionnaire used was derived from the GHPSS. A total of 600 students were invited in the study while 470 returned questionnaires and participated in the study. Descriptive statistics were used to present the data. The Fisher’s exact test was used to test the significance and a p-value<0.05 was considered significant. Results: The prevalence rate of smoking among students was 16.9% (95% CI 13.2-20). Current smokers were 79 students, 28.2 % males, and 7.7 % females. The study showed that 55.5% of students smoke less than a pack of cigarettes per day. Almost half of them (47.6%) who smoke reported to have a smoker inside the family. This study also revealed that 74.7% of respondents smoke in the presence of non-smokers on daily bases. Conclusion: Despite threating their own health, smokers also cause noxiousness to the society and medical students should be role models for the others by not smoking. Even though the percentage doesn’t show a high rate of smokers in Medical University of Prishtina, still we need to pay attention to bad smoking habits and try...